American psychosis : how the federal government destroyed the mental illness treatment system - Torrey, E. Fuller (Edwin Fuller), 1937- (Oxford University Press, 2014)
In 1963, President John F. Kennedy described sweeping new programs to replace "the shabby treatment of the many millions of the mentally disabled in custodial institutions" with treatment in community mental health centers. This movement, later referred to as "deinstitutionalization," continues to impact mental health care. Fifty years after Kennedy's speech, the author provides an inside perspective on the birth of the federal mental health program. He draws on his own first-hand account of the creation and launch of the program, extensive research, one-on-one interviews with major figures involved in the legislation, and recently unearthed audiotapes of interviews with major figures involved the legislation. As such, this book provides historical material previously unavailable to the public. He also examines the political maneuverings required to pass the legislation, the Kennedys' involvement in the policy and that of other major players, the responsibility of the state versus the federal government in caring for the mentally ill, and how closing institutions has ultimately resulted not in better care, but in underfunded programs, neglect, and higher rates of community violence. In this book the author presents an account of the history and present day failings of our mental health treatment system. As he argues, it is imperative to understand how we got here in order to move forward towards providing better psychatric care for the most vulnerable. -- From book jacket